The relationship of knowledge about Diabetes Mellitus risk factors with the healthy lifestyle among nursing students - Malini, Hema; Hazira, Khairunnisa; Kardila, Intan Yullya; Lenggogeni, Devia Putri (Jurnal Kesehatan - STIKes Prima Nusantara, 2024)
Background: The incidence of Type 2 Diabetes Mellitus (T2DM) in young age groups continues to increase. Student knowledge about diabetes risk factors is still in the category of lacking so that students cannot apply healthy lifestyle implementation behaviors correctly. Purpose: The study aims to determine the relationship between knowledge and healthy living behavior in students of the Faculty of Nursing, Andalas University. Methods: The design of this study was cross sectional. The sample number was 218 students of the Faculty of Nursing and used the propotional random sampling technique. The research data was collected with DM risk factor knowledge questionnaire and healthy lifestyle application questionnaire through Google form media. Data analysis using chi-square test. Result: Researchers found that there was a relationship between knowledge of DM risk factors and the application of a healthy lifestyle (p = 0.002), where knowledge about DM risk factors was obtained in the sufficient category with the application of a low healthy lifestyle. Conclusion: Therefore, it is still necessary to increase student knowledge about diabetes mellitus risk factors.